EDUCATION LINEARITY: THE SHACKLE OF DISRUPTION ERA IN INDUSTRIAL REVOLUTION 4.0 FROM THE DEFENSE PERSPECTIVE - Elies Fitriani; Herlina Tarigan; Deni Dadang Ahmad Rajab (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
The era of the industrial revolution 4.0 has had a big impact on changing the order of life or global disruption. In Indonesia, almost all tertiary institutions apply linearity in recruiting teaching staff and academics when they are going to a higher level. The linearity of the study program according to the Circular of the Ministry of Research, Technology and Higher Education of the Republic of Indonesia Number 696/E.E3/MI/2014 is the suitability of the background knowledge obtained in the bachelor, master and doctoral degree program with the knowledge that will be taught at the teaching place to achieve competence or learning outcomes at the teaching place. The challenge of life today is to answer actual global issues that can no longer be viewed from a monodisciplinary point of view but must be viewed from a transdisciplinary and multidisciplinary point of view. This study is a qualitative approach, that leads to the situation and the individual holistically. This type of research is descriptive in the form of a literature study using primary and secondary sources. The problem is the defense system nowadays is more complex with the new perspective of the 5th generation war. The 5th generation war needs a comprehensive approach in the defense systems including bioinformatics, biomedical, psychology, industrial, chemical, biology, and others. Linearity in the defense educational system could be a shackle for the defense system to encounter the industrial revolution and 5th generation war. Indonesia Defence University could be an example where defense is viewed from the spirit of collaboration and cooperation between multidisciplinary, transdisciplinary, and interdisciplinary approaches. By opening its doors to undergraduates, the university can start building a much-needed core of human resources equipped to defend the country and also new hope for a comprehensive perspective in the defense system.